2023
DOI: 10.1186/s12866-023-02948-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamase-producing E. coli from retail meat and workers: genetic diversity, virulotyping, pathotyping and the antimicrobial effect of silver nanoparticles

Heba A. Ahmed,
Ibrahim Elsohaby,
Amina M. Elamin
et al.

Abstract: Background The spread of extended-spectrum β-lactamases (ESBL) producing E. coli from food animals and the environment to humans has become a significant public health concern. The objectives of this study were to determine the occurrence, pathotypes, virulotypes, genotypes, and antimicrobial resistance patterns of ESBL-producing E. coli in retail meat samples and workers in retail meat shops in Egypt and to evaluate the bactericidal efficacy of silver nanoparticles (AgNPs-H2O2) against multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Similarly, in Nigeria, a high frequency of ESBL-producing E. coli was detected on the hands of retailers (40.6%) and butchers (75.0%) who handled pork [64]. Comparable findings were reported among food handlers in Ethiopia [65,66] and Egypt [67]. In Tunisia, stool samples collected from 2135 food handlers revealed that 419 (19.63%) E. coli isolates were considered ESBL producers, with a notable prevalence of strains belonging to ST131.…”
Section: Esbl-producing E Coli In Animal-derived Foodsmentioning
confidence: 92%
“…Similarly, in Nigeria, a high frequency of ESBL-producing E. coli was detected on the hands of retailers (40.6%) and butchers (75.0%) who handled pork [64]. Comparable findings were reported among food handlers in Ethiopia [65,66] and Egypt [67]. In Tunisia, stool samples collected from 2135 food handlers revealed that 419 (19.63%) E. coli isolates were considered ESBL producers, with a notable prevalence of strains belonging to ST131.…”
Section: Esbl-producing E Coli In Animal-derived Foodsmentioning
confidence: 92%
“…coli infections among humans are associated with phylogroups B2 and, to a lesser extent, D, while phylogroups A and B1 are often associated with commensal E. coli. , …”
Section: Introductionmentioning
confidence: 99%
“…coli strains belong to different phylogenetic groups, which are intertwined with virulence factors and the genetic substructures associated with different phylogeny, phenotypic, and genotypic traits. , The most recent phylogenetic grouping of E. coli describes eight phylogroups (A, B1, B2, C, D, E, F, and G) based on the presence or absence of four genes ( ChuA , yjaA , TspE4.C2 , and arpA ), with specific lifestyles and/or hosts attributed to each. Typically, E. coli infections among humans are associated with phylogroups B2 and, to a lesser extent, D, while phylogroups A and B1 are often associated with commensal E.…”
Section: Introductionmentioning
confidence: 99%
“…Commensal intestinal bacteria, such as Escherichia coli, have been described as good fecal indicators [9]; moreover, this bacterial species includes relevant multidrug-resistant strains, including carbapenemresistant and extended-spectrum β-lactamases-producing strains, with known resistance to fluoroquinolones, aminoglycosides, and trimethoprim-sulfamethoxazole [10]. Apart from including commensal strains, enteric E. coli can be categorized into distinct pathotypes according to their pathogenicity and virulence traits, which include enterohemorrhagic (EHEC), enteropathogenic (EPEC), enterotoxigenic (ETEC), enteroinvasive (EIEC), enteroaggregative (EAEC), diffusely adherent (DAEC), and adherent-invasive (AIEC) E. coli [11,12]. Together, these traits make E. coli a relevant model for investigating resistance transmission pathways within ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%